PEREMPUAN DENGAN DISABILITAS DALAM MENGAKSES PELAYANAN KESEHATAN - Butarbutar, Dina Elisabet (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2022)
This study examines the barriers, challenges, and special needs of women with disabilities in accessing health services in Jambi. Based on in-depth interviews and observations, it was found that limited physical accessibility, limited information and communication, as well as stigma and discrimination were the main obstacles. Women with disabilities often do not receive adequate care because existing health services are not tailored to their specific conditions. These findings point to the need for improved disability-friendly infrastructure, training for health workers, and the development of more inclusive health programs. Involving women with disabilities in the health care planning and evaluation process is also important to ensure their needs are met. Public awareness and education about disability need to be increased to reduce stigma and discrimination, thereby creating a more inclusive and supportive environment for women with disabilities.